O-GlcNAc modification regulates autophagy and apoptosis in endometriosis - Xiaohan Jin; Yali Feng; Lei Xu; Jing Li; Linping Fan; Jinge Li; Runyuan Liu; Qing Yang; Ying Kong; Yuhong Shang (Functional & Integrative Genomics, 2026)

Decoding the partitioning behavior of poly- and perfluoroalkyl substances: Insights from human liver and blood biomonitoring with machine learning - Linping Cao; Yishu Zheng; Wenfei Yu; Jiaqi Shao; Yu Fu; Yating Liu; Weichen Zhang; Jiamian Fang; Yuanchen Chen; Hangbiao Jin (Environmental Pollution, 2026)

Continuous hollow spiral microfibers with embedded microchannels for synergistically enhanced atmospheric water harvesting and storage - Yuqiu Guo; Yalan Liu; Chuanjiyue Zhou; Ze Lv; Qianqian Wang; Wei Wu; Bolin Ji; Linping Zhang; Xueling Feng; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2026)

Moisture-regulated pad dyeing of cotton fabrics: mechanistic insights into water migration and energy-efficient fixation - Yalan Liu; Wei Wu; Bolin Ji; Linping Zhang; Yi Zhong; Hong Xu; Zhiping Mao (Journal of Cleaner Production, 2026)

Contrasting strategies of two Camellia oleifera cultivars in shaping arbuscular mycorrhizal fungi communities under different phosphorus forms - Yuxuan Huang; Xin You; Adam Frew; Fei Wu; Linping Zhang; Xinping Liu; Jiaoping Xing (European Journal of Soil Biology, 2026)

Decoding synergy: from the precise construction of dual-atom catalysts to synergistic engineering - Yaning Fu; Linping Shi; Dongxue Liu; Yipeng Liu; Tong Liu; Yunyin Niu; Youcai Lu; Qingchao Liu (Chemical Engineering Journal, 2026)

Identification of rice paddy field morphology following the collapse of Neolithic culture in the Taihu Lake Plain, the Lower Yangtze River - Haiming Li; Xuan Yi; Huiru Lian; Xuyang Zhang; Duo Zheng; Xuanyi Zhang; Linping Ren; Liu Yang; Zhiping Zhang; Rongfang Song; Zhikun Ma; Harry F. Lee; et al. (Journal of Geographical Sciences, 2026)

Efficient cellulose evaporator inspired by plant and tumbler for robust solar desalination - Shaoting Chen; Yuqiu Guo; Yalan Liu; Linping Zhang; Wei Wu; Hong Xu; Zhiping Mao (Desalination, 2026)

PEDOT: PSS-based fabric with adjustable emissivity for multi-scenario infrared stealth - Huimin Tan; Jinru Liu; Jian Cao; Wei Wu; Bolin Ji; Linping Zhang; Yi Zhong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2026)

Genotypic differences in root-associated microbiomes and metabolites regulate soil available phosphorus in Camellia oleifera - Yuxuan Huang; Fei Wu; Xingping Liu; Linping Zhang; Bo Chen; Shaohua Huang; Jia Cao; Xin You (Rhizosphere, 2025)

Enhancing surface electron donation of single-atom copper catalyst for promoting CO2 electroreduction to CH4 - Bowen Wu; Lu Song; Hairui Ma; Kewei Zhang; Mingtai Liu; Anxiang Guan; Zhengzheng Liu; Chao Yang; Naixin Lyu; Gengfeng Zheng; Linping Qian (Chemical Engineering Journal, 2025)

Janus-structured thermally conductive radiative cooler for electronic devices heat dissipation - Xiuyan Yan; Jinru Liu; Linping Zhang; Yi Zhong; Bolin Ji; Wei Wu; Bijia Wang; Xueling Feng; Liduo Rong; Hong Xu; Zhiping Mao (Chemical Engineering Journal, 2025)

PDZD8 Dysregulation Mediates RVLM Neuronal Hyperexcitation Via Activation of Ca2+-Calpain-2 Signaling in Stress-Induced Hypertension - Tianfeng Liu; Linping Wang; Lei Tong; Zhangyan Ren; Bingjie Zhao; Haisheng Liu; Wen Lu; Haili Zhang; Shuai Zhang; Dongshu Du (Molecular Neurobiology, 2025)

Optimization of Phaeodactylum tricornutum cultivation for enhancing mariculture wastewater treatment and high value product recovery using Box–Behnken design - Feng You; Yiwei Fan; Linping Tang; Xiangrong Liu; Chunji Jin; Yangguo Zhao; Yi Wang; Liang Guo (Process Safety and Environmental Protection, 2025)

POD-like nanozyme constructed from perspective of charge transfer engineering for biosensing of magnetic separation treated Listeria monocytogenes - Weiqiang Li; Xiaoyun Xu; Yang Song; Linping Fan; Jin Huang; Luyu Yang; Yang Liu; Hengyi Xu (Food Chemistry, 2025)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Gas-liquid interface derived lightweight and twistable BiOI/In2O3/tape assembly for photocatalytic NO removal - Liyang Zhang; Yangqin Gao; Ziyu Teng; Yida Liu; Xinming Liu; Chuanbo Cong; Kezhen Lai; Linping Li; Jipeng Dong; Ning Li; Lei Ge (Chemical Engineering Journal, 2024)

Effects of different biogas slurry application patterns on nitrogen and phosphorus losses in a paddy field - Ming Li; Yinxiu Liu; Linping Luo; Shanshan Ying; Peikun Jiang (Paddy and Water Environment, 2024)

Parabens promotes invasive properties of multiple human cells: A potential cancer-associated adverse outcome pathway - Linping Wang; Luyi Chen; Daniel Schlenk; Feixue Li; Jing Liu (Science of The Total Environment, 2024)

Enhanced NMDA receptor pathway and glutamate transmission in the hippocampal dentate gyrus mediate the spatial learning and memory impairment of obese rats - Dingding Lv; Bin Xiao; Huaying Liu; Linping Wang; Yingshun Li; Yin Hua Zhang; Qinghua Jin (Pflügers Archiv - European Journal of Physiology, 2024)
Obesity has been linked with the impairment of spatial memory and synaptic plasticity but the molecular mechanisms remained unidentified. Since glutamatergic transmission and NMDA receptor neural pathways in hippocampal dentate gyrus (DG) are essential in the learning and memory, we aimed to investigate glutamate (Glu) and NMDA receptor signaling of DG in spatial learning and memory in diet-induced obesity (DIO) rats. Spatial learning and memory were assessed via Morris water maze (MWM) test on control (Ctr) and DIO rats. Extracellular concentration of Glu in the DG was determined using in vivo microdialysis and HPLC. The protein expressions of NMDA receptor subunit 2B (NR2B), brain-derived neurotrophic factor (BDNF), the activation of calcium/calmodulin-dependent kinase II (CaMKII) and cAMP-response-element-binding protein (CREB) in the DG were observed by western blot. Spatial learning and memory were impaired in DIO rats compared to those of Ctr. NR2B expression was increased, while BDNF expression and CaMKII and CREB activation were decreased in DG of DIO rats. Extracellular concentration of Glu was increased in Ctr on the 3rd and 4th days of the MWM test, but significant further increment was observed in DIO rats. Microinjection of an NMDA antagonist (MK-801) into the DG reversed spatial learning and memory impairment. Such effects were accompanied by greater BDNF expression and CaMKII/CREB activation in the DG of DIO rats. In conclusion, the enhancement of Glu-NMDA receptor transmission in the hippocampal DG contributes to the impairment of spatial learning and memory in DIO rats, maybe via the modulation of CaMKII-CREB-BDNF signaling pathway.

Disruption of gonadotropin hormone biosynthesis by parabens: A potential development and reproduction-associated adverse outcome pathway - Linping Wang; Xiaochen Liu; Manqi Zhao; Feixue Li; Jing Liu (Environmental Pollution, 2024)

Effects of pharmaceutical and personal care products on pubertal development: Evidence from human and animal studies - Linping Wang; Xiaoqing Ye; Jing Liu (Environmental Pollution, 2024)

A simulation-optimization approach based on the compound eutrophication index to identify multi-nutrient allocated load - Yanqun Yang; Keqiang Li; Shengkang Liang; Guohong Lin; Cheng Liu; Jixin Li; Linping Xie; Yanbin Li; Xiulin Wang (Science of The Total Environment, 2024)

The responding mechanism of indigenous bacteria in municipal wastewater inoculated with different concentrations of exogenous microalgae - Xinyue Yang; Linping Liu; Xudong Liu; Shulian Xie; Jia Feng; Junping Lv (Journal of Environmental Management, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

The diabetogenic effects of pesticides: Evidence based on epidemiological and toxicological studies - Yile Wei; Linping Wang; Jing Liu (Environmental Pollution, 2023)

Spatial Distribution and Seasonal Variation of Hypoxic Zone in the Eastern Equatorial Indian Ocean - Linping Xie; Baodong Wang; Ming Xin; Ying Wang; Xia Sun; Qinsheng Wei; Lin Liu; Chao Yuan (Journal of Ocean University of China, 2023)

Synergy between Mo dopants and Ni vacancies in NiOOH for enhanced oxygen evolution reaction - Xiaoyi Dou; Ding Yuan; Xiaopeng Liang; Kepeng Song; Riming Hu; Lei Zhang; Jagadish Chandra Roy; Xuchuan Jiang; Hua Kun Liu; Yuhai Dou; Linping Yu (Chemical Engineering Journal, 2023)

Influence of inlet placement on the hydrodynamics of the dual-drain arc angle tank for fish growth - Haibo Liu; Boru Xue; Xiaozhong Ren; Zhangying Ye; Linping Yu; Qian Zhang (Aquacultural Engineering, 2023)

Identification of a novel frameshift mutation in the SCNN1B causing Liddle syndrome - Yi Qu; Yiting Lu; Di Zhang; Xinchang Liu; Peng Fan; Jiexin Chen; Hanbo Zhang; Kunqi Yang; Tao Tian; Yi Zhou; Qiongyu Zhang; Yu Zhang; et al. (Science Bulletin, 2023)

Factors associated with dysglycemia and its post-surgical resolution in patients with pheochromocytomas - Lin Zhao; Xu Meng; Qiongyu Zhang; Yi Zhou; Ting Zhang; Tao Tian; Hua Fan; Huadong Zhu; Yecheng Liu; Fang Luo; Linping Wang; Weixian Yang; et al. (Science China Life Sciences, 2023)

Multiple Frequency Contrast Source Inversion Method for Vertical Electromagnetic Profiling: 2D Simulation Results and Analyses - Jinghe Li; Linping Song; Qing Huo Liu (Pure and Applied Geophysics, 2016)

Benzene containing polyhydroxyalkanoates homo- and copolymers synthesized by genome edited Pseudomonas entomophila - Rui Shen; LongWei Cai; DeChuan Meng; LinPing Wu; Kai Guo; GuoXing Dong; Lei Liu; JinChun Chen; Qiong Wu; GuoQiang Chen (Science China Life Sciences, 2014)